Cover Image. (11th January 2023) - Zhang, Guofang; Zhou, Jinzhi; Peng, Yan; Tan, Zengdong; Zhang, Yuting; Zhao, Hu; Liu, Dongxu; Liu, Xiao; Li, Long; Yu, Liangqian; Jin, Cheng; Fang, Shuai; et al.
Abstract : The cover image is based on the Original Article High‐throughput phenotyping‐based quantitative trait loci mapping reveals the genetic architecture of the salt stress tolerance of Brassica napus by Guofang Zhang et al., https://doi.org/10.1111/pce.14485 .